Unlocking the investment impact of biomass energy utilization on environmental degradation for an isolated island - Gyamfi, B.A.; Agozie, D.Q.; Bein, M.A.; et al. (International Journal of Energy Sector Management, 2021)
Purpose: Discussions on environment-friendly production connected with the concerns of growing biomass emissions have gained much attention. In this regard, this study aims to explore the issue of biomass energy consumption and its related emission effects on the economic and environmental well-being of the economy of Cyprus. Design/methodology/approach – This study sources time-series data on specific variables from the Global Material Flow and the World Bank’s World Development Indicators (WDI, 2020) between 1990 and 2016. The Robust least square (ROB-L2) in conjunction with Pesaran autoregressive distributed lag (ARDL) methodology analysis techniques was used in addition to the Granger causality tests to examine the direction of causal flow between the variables under consideration. Findings: The results indicate that biomass energy usage in the long run reduces pollution and negatively correlates with CO2 emissions level. Also, the decline in emission is influenced by increased foreign direct investment (FDI); thus, activities of foreign investors contribute to combating emission in the country. According to empirical results, non-renewable energy consumption showed both positive and negative influences on increased emission level, whereas economic growth is increasing carbon dioxide emission for the case of Cyprus.Originality/value: This study applies current, reliable data that offers renewed insights and sheds light on the state of affairs on biomass utilization from a developing country perspective. Additionally, it extends the discourse on the impact of biomass utilization on CO2 emissions by considering the impact of FDI, trade flow and energy consumption in a carbon-income function built on the liner version of the environmental Kuznets curve hypothesis. Although this is by no means exhaustive, the study pioneers the discourse on how FDI and biomass utilization, among other relevant variables, influences carbon dioxide emission.
Research Article
Keywords: Biomass energy; Carbon reduction; Non-renewable energy